Manajemen Qur’ani Tentang Penggunaan Waktu Dalam Bingkai Pendidikan Islam - Abdur Rohman (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2018)
Humans have different fates. Among them there are already successful in their teens, when the head of three, the head of four even some who until the age of twilight remain ordinary people. Why the difference occurs, even though the time given to them is the same. The only difference is the utilization. For that, taking the best possible time becomes the key. While the Qur'an provides a way how to become a lucky person. This article uses qualitative research-literature with thematic tafsir approach that is by collecting the verses related to the theme, then interpret it. God swears by the time that success is achieved when the four components are fulfilled: faith, doing positive, counseling and being consistent on the right track and being patient. In the implementation of general education and Islamic education in particular, the issue of time management is also an important part of the success of these educational activities. There are no few signals in the Qur'an or Hadith of the Prophet (SAW) which emphasizes the importance of time management, even in the Qur'an there is a letter deliberately named with time (Al-'Arr).